The eye of excellence : achieving excellent results with a Project Excellence Model - Anna Kristín Kristinsdóttir 1986-; Ásta Lára Jónsdóttir 1982- (2017)
Project excellence and how it can be achieved, has been a topic attracting much research interest. Even though no clear and common distinction has been made on what project success entails, many tools have been developed to assist the enhancement of project success, some even pushing for excellence. The Project Excellence Model is one of these tools and has been used with good results for many years in assessing the excellence of projects applying for IPMA’s yearly Project Excellence Awards. The model has been used for several years, however, its literature foundation is weak as not much has been written about it and few have researched it. The model has never been applied to a project in Iceland. It is for this reason that it was both challenging and exciting as a base for this thesis to apply the model in a case study for The National Power Company of Iceland, Landsvirkjun. The objective was not only to evaluate a large construction project but also to study the model and its assessment process in order to illuminate its strengths and opportunities for improvement. Since the model has mostly been used in an award process it is also interesting to evaluate if the model can be used to achieve excellence in projects and project management and if it can be useful to elucidate the critical factors in project preparation and management in Icelandic projects. The case study and research results show that the model can indeed be applied and used to enhance project performance in order the achieve a successful and even excellent outcome regardless of an international award process. In addition, the model covers critical factors in project preparation, and can function as an iteration for continuous improvement during the entire project lifecycle.